Sex, boldness and stress experience affect convict cichlid, Amatitlania nigrofasciata, open field behaviour - Moscicki, Michele K.; Hurd, Peter L. (My University, 2015)
How an organism deals with stressors is an integral component of survival. Recent research has shown that differences in a well-studied personality axis in fish, the shy–bold axis, relate to stress-coping behaviours. Bold fish tend to cope in a proactive manner (e.g. fighting) while shy fish cope more reactively (e.g. freezing). Because bold fish behave in a more risk-prone manner, it is likely that they encounter more stressors on average than shy fish. Greater exposure to stressful conditions may result in bold fish being less behaviourally sensitive to stressors (i.e. stress resilience). To investigate the idea of stress exposure leading to resilience, we examined whether fish personality (i.e. more bold or shy) affected anxiety-related behaviour in an open field task after fish had been exposed to a net-chasing stressor. We investigated open field behaviour in the presence and absence of a stressor (i.e. damage-induced alarm cues) to determine whether bolder fish would cope differently with a stressor than shy fish after recent stress exposure of a different type. Furthermore, we examined whether asymmetry in the habenula, an asymmetrical nucleus related to behavioural responses to stress and anxiety, is related to behaviour in the presence of stressors. We found no relationship between habenular asymmetry and behaviour in the open field. Net chasing increased activity in the open field for both sexes. We found an interaction between stress exposure and freezing behaviour in females but not in males. When females were not net-chased, shyer females showed a decrease in freezing behaviour when exposed to alarm cues, whereas bolder females showed no change in behaviour. When females were net-chased, there was no difference in freezing behaviour between bolder and shyer fish. We suggest that different parental care roles in this species lead to differential perceptions of the threat of stress between the sexes.
Keywords: convict cichlid; damage-induced alarm cue; habenula; open field; resilience; sex difference; shy–bold axis; stress